2021
DOI: 10.1039/d1ra02143e
|View full text |Cite
|
Sign up to set email alerts
|

Novel fabrication of a yeast biochar-based photothermal-responsive platform for controlled imidacloprid release

Abstract: The yeast biochar-based platform exhibited excellent photothermal conversion capability, and realized light-triggered controlled release of IMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Among them, near-infrared (NIR) light-triggered systems are attracting attentions because NIR light can employ natural sunlight and be regulated remotely and easily by adjustable wavelength and intensity [18,33]. As a photothermal conversion reagent from pyrolysis products of agricultural wastes, biochar is reproducible, biocompatible, and low-cost [34][35][36], in sharp contrast to other photothermal reagents like Au nanoparticles [37], carbon nanotubes [38], graphene [39] and Fe3O4 nanoparticles [40]. Taking this advantage into account, in this work we have fabricated a NIR light responsive polysulfide carrier (SOCT, the acronym of each raw material) through inverse vulcanization of sulfur and soybean oil in one-pot, encapsulating biochar and tebuconazole (Teb) as the photothermal conversion reagent and model pesticide, respectively, 5 as illustrated in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, near-infrared (NIR) light-triggered systems are attracting attentions because NIR light can employ natural sunlight and be regulated remotely and easily by adjustable wavelength and intensity [18,33]. As a photothermal conversion reagent from pyrolysis products of agricultural wastes, biochar is reproducible, biocompatible, and low-cost [34][35][36], in sharp contrast to other photothermal reagents like Au nanoparticles [37], carbon nanotubes [38], graphene [39] and Fe3O4 nanoparticles [40]. Taking this advantage into account, in this work we have fabricated a NIR light responsive polysulfide carrier (SOCT, the acronym of each raw material) through inverse vulcanization of sulfur and soybean oil in one-pot, encapsulating biochar and tebuconazole (Teb) as the photothermal conversion reagent and model pesticide, respectively, 5 as illustrated in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Some recent research showed that the coexisting ions had no obvious effect on the release behavior of agrochemicals. 41,42 When some alkaline ions are present in large quantities (e.g., CO 3…”
Section: Resultsmentioning
confidence: 99%
“…Besides, there are many coexisting ions in the soil. Some recent research showed that the coexisting ions had no obvious effect on the release behavior of agrochemicals. , When some alkaline ions are present in large quantities (e.g., CO 3 2– ), it may cause the accelerated migration of salicylic acid. However, the disintegration rate of carrier is still the key factor governing the SA release behavior.…”
Section: Resultsmentioning
confidence: 99%
“…The photothermal agents can absorb light and effectively convert light energy into heat energy, resulting in the rise of temperature of the system and thus stimulating the release of pesticides in such a system. [20][21][22] To date, few photothermal controlledrelease pesticide delivery systems have been reported because the common photothermal agents, such as gold nanorods, graphene, and so forth, with high costs and the shortcoming of difficult degradation, are mostly unsuitable for constructing pesticide delivery systems for vast agricultural application. [23][24][25][26] Polydopamine (PDA) possesses a photothermal conversion efficiency of 40%, and the virtues of low cost, easy fabrication, biocompatibility, and biodegradability.…”
Section: Introductionmentioning
confidence: 99%